2013
DOI: 10.1186/1744-9081-9-32
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of drowsiness and reaction time during intermittent Ramadan fasting in young men: a case-crossover study

Abstract: BackgroundRamadan fasting and its attendant lifestyle changes induce changes in the circadian rhythm and in associated physiological and metabolic functions. Previous studies that have assessed psychomotor performance during Ramadan fasting have reported conflicting results. Therefore, we designed this study to objectively assess the effects of intermittent fasting during and outside Ramadan (to control for lifestyle changes) on drowsiness, blink total duration and mean reaction time (MRT) test while controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 47 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…It is important to note that despite reporting impacted sleep architecture/schedule in Muslims fasting during Ramadan, previous investigators [ 36 , 39 ] reported no effect on the arousal index or daytime sleepiness. Another study also showed no impact of RIF on daytime sleepiness, drowsiness or vigilance [ 40 ], suggesting no potential major effect of these variables on cognitive function. In the light of the present study results, it is speculated that the cyclists were probably not in negative alertness and vigilance states.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that despite reporting impacted sleep architecture/schedule in Muslims fasting during Ramadan, previous investigators [ 36 , 39 ] reported no effect on the arousal index or daytime sleepiness. Another study also showed no impact of RIF on daytime sleepiness, drowsiness or vigilance [ 40 ], suggesting no potential major effect of these variables on cognitive function. In the light of the present study results, it is speculated that the cyclists were probably not in negative alertness and vigilance states.…”
Section: Discussionmentioning
confidence: 99%
“…These periods were specified in accordance with the literature. 24 Completing the questionnaire and the fatigue scale took approximately 10 to 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Another study assessed the impact of diurnal IF during Ramadan on drowsiness under controlled conditions with a fixed light/dark exposure, caloric intake, sleep/wake schedule and sleep duration via measuring total blink duration (measured using infrared reflectance (IR) oculography) and the mean reaction time (MRT) 61. The results of this study showed that diurnal intermittent fasting had no impact on drowsiness or vigilance 61…”
Section: Daytime Sleepinessmentioning
confidence: 99%